Prognostic value of negative stress cardiac magnetic resonance imaging in patients with moderate-severe coronary artery stenosis - Haney, Ailís Ceara; Salatzki, Janek; Hund, Hauke; Friedrich, Matthias; Giannitsis, Evangelos; Frey, Norbert; Steen, Henning; Loßnitzer, Dirk; Riffel, Johannes; André, Florian (Frontiers in Cardiovascular Medicine, 2023)
ObjectiveThis study aims to evaluate the prognostic value of stress cardiac magnetic resonance (CMR) without inducible ischemia in a real-world cohort of patients with known severe coronary artery stenosis.BackgroundThe prognosis of patients with severe coronary artery stenosis and without inducible ischemia using stress CMR remains uncertain, even though its identification of functionally significant coronary artery disease (CAD) is excellent.Materials and methodsPatients without inducible ischemia and known CAD who underwent stress CMR between February 2015 and December 2016 were included in this retrospective study. These patients were divided into two groups: group 1 with stenosis of 50%-75% and group 2 with stenosis of >75%. The primary endpoint was defined as the occurrence of a major adverse cardiovascular event (MACE) [cardiac death, non-fatal myocardial infarction (MI), percutaneous coronary intervention (PCI), or coronary artery bypass grafting (CABG)].ResultsReal-world data collected from 169 patients with a median age of 69 (60-75) years were included. The median follow-up was 5.5 (IQR 4.1-6.6) years. Events occurred after a mean time of 3.0 ± 2.2 years in group 1 and 3.7 ± 2.0 years in group 2 (p = 0.35). Sixteen (18.8%) patients in group 1 and 23 (27.4%) patients in group 2 suffered from MACE without a significant difference between the two groups (p = 0.33). In group 2, one cardiac death (1.2%), seven non-fatal MI (8.3%), 15 PCI (17.9%), and one CABG (1.2%) occurred.ConclusionThe findings of this pilot study suggest that long-term outcomes in a real-world patient cohort with known severe and moderate coronary artery stenosis but without inducible ischemia were similar. Stress CMR may provide valuable risk stratification in patients with angiographically significant but hemodynamically non-obstructive coronary lesions.